Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1039/c5nr00555h
|View full text |Cite
|
Sign up to set email alerts
|

A novel form of β-strand assembly observed in Aβ33–42adsorbed onto graphene

Abstract: Peptide assembly plays a seminal role in the fabrication of structural and functional architectures in cells. Characteristically, peptide assemblies are often dominated by β-sheet structures, wherein component molecules are connected by backbone hydrogen bonds in a parallel or an antiparallel fashion. While β-rich peptide scaffolds are implicated in an array of neurodegenerative diseases, the mechanisms by which toxic peptides assemble and mediate neuropathic effects are still poorly understood. In this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…The hydrophobic interaction, rather than backbone hydrogen bonding, is crucial for the Aβ42 interaction, consistent with recent evidence. 50 Qualitatively, these findings are in agreement with the characterization of early-stage Aβ42 aggregates by CD and ThT fluorescence that show that the oligomers have a low β-content. 17,51 …”
Section: Discussionsupporting
confidence: 88%
“…The hydrophobic interaction, rather than backbone hydrogen bonding, is crucial for the Aβ42 interaction, consistent with recent evidence. 50 Qualitatively, these findings are in agreement with the characterization of early-stage Aβ42 aggregates by CD and ThT fluorescence that show that the oligomers have a low β-content. 17,51 …”
Section: Discussionsupporting
confidence: 88%
“…Accumulating evidence has shown that Aβ peptides can adsorb onto the cell membrane , and other material surfaces and that their self-assembly can be significantly influenced by these substrate surfaces. A better understanding of the interaction between Aβ and those surfaces thus might provide new insights to the underlying mechanism of the peptide assembly as well as the development of potential therapeutic strategies against AD.…”
Section: Introductionmentioning
confidence: 99%
“…Both graphene and MoS 2 nanosheets have a highly hydrophobic surface with large water contact angles (despite that MoS 2 has partial charges on Mo and S atoms), offering a biomimetic environment for protein binding when interfaced with water (Mathesh et al, 2016;Gu et al, 2017;Zhang et al, 2017). Previous studies have observed a variety of effects of graphene on proteins, including disruption of protein structures (Zuo et al, 2011;Chong et al, 2015;Wang et al, 2015), enhancement of enzymatic activity (Mathesh et al, 2016), and potential interference of protein-protein interactions (Luan et al, 2015(Luan et al, , 2016aFeng et al, 2016). Comparatively, there are less studies on MoS 2 's effect on proteins partly due to the lack of appropriate potential function parameters for MoS 2 simulation.…”
Section: Introductionmentioning
confidence: 99%